Performativity, Queer Objects and Radical Creativity - Brickell, Chris (Italian Sociological Review, 2025)
During the early 1990s, Judith Butler’s concept of performativity radically altered the way scholars thought about gender and sexuality, but by 2020 new meanings had attached themselves to the term. This article works towards a revitalised queer engagement with performativity, seeking to reinstate Butler’s focus on constitutive power while questioning the extent to which performativity necessarily reinscribes social norms. By drawing on the turns to affect and objects, the article explores the performative and sometimes radical possibilities that arise out of creative practices of the self. A discussion of queer objects, including books, domestic ephemera, clothing, and items from AIDS activism, suggests material culture and affective practices may intersect with performative impulses, providing the conditions for the constitution of new modes of sexual and social life.